Kedatangan Islam di Dana Mbojo, Bima (TINJAUAN HISTORIS): Islam, Mbojo, Historical Overview, Bima - hamzah, saidin (Al-Hikmah, 2022)
This study aims to reconstruct the history of the early entry of Islam in Dana Mbojo (Bima). The research uses historical methods. To reveal historical facts, the research was conducted at Dana Mbojo (Bima) West Nusa Tenggara using several approaches: historical, anthropological and sociological approaches. Data collection was obtained through interviews, observation and documentation. The study also used library research through primary and secondary data. Primary data was obtained from BO’ Sangaji Kai, documents and other authentic relics, while secondary data was obtained from books, journals, articles, theses and theses. The data that has been obtained is processed and analyzed in depth. The results showed that: The early history of the entry of Islam in Dana Mbojo (Bima) occurred in three stages, namely: 1) The occurrence of the first contact with traders from Demak. 2) Overseas carried out by indigenous traders to Ternate and Tidore. 3) The arrival of empathetic envoys from the kingdom of Gowa to the port of Sape and Islamizing the local community. The role of scholars and sultans in building the existence of Islam in Bima so that there are great historical relics such as the historic Temba Romba, La Kai Mosque in Kamina and ancient langgar in Malay village. The implication of this research is that there are many shortcomings, due to the lack of data that the authors get. The book BO’ Sangaji Kai only describes in general the history of Bima and uses Malay. To address this, the data obtained through lisah sources (oral history). Temba Romba and the Kamina mosque are historical evidences of the presence of Islam in Bima. Therefore, it is hoped that the government’s role in maintaining and caring for historical sites is for the benefit of the general public. Because a large area is an area that respects its ancestral heritage.